The unsustainability of sustainability: a new perception of applied ecology against the granfalloon’s mission - Fierro, Angelo (BORNH Bulletin of Regional Natural History, 2021)
The unsustainability of sustainability wants to underline the improper and widespread use of a complex concept that cannot be trivialized through the proposal of technological solutions. Although technological solutions represent “comfortable” tools for social reassurance, the risk is a social drift generated by the phenomenon of the “granfalloon”. Behind the technological solutions there are new market proposals, which have nothing to do with the real resolution of the sustainability of the global socio-economic system. The perception of the whole socio-economic system as a single metabolic socio-ecological system, makes us interpret the role of technological solutions differently. The knowledge we have gained over the last 50 years on the functioning of natural systems represent consolidated bases for interpreting and providing solutions on the sustainability of mankind. This perception, while providing uncomfortable solutions, should change the perception of applied ecology within the academy community. Therefore, applied ecology no longer as a study of human effects on the ecosphere, but as a discipline that teaches mankind how to structure its socio-economic metabolism compatibly with the constraints imposed by the ecosphere.